The Flintstones [videorecording (DVD)] - Cohen, Bruce, 1961-; Parker, Tom S.; Jennewein, Jim; De Souza, Steve; Levant, Brian; Goodman, John, 1952-; Moranis, Rick; Perkins, Elizabeth, 1960-; O'Donnell, Rosie; MacLachlan, Kyle, 1959-; Berry, Halle; Taylor, Elizabeth, 1932-2011; et al. (Universal Home Video, 1999)
After an aptitude test mix-up, Fred Flintstone trades his job as bronto-crane operator for a vice presidency, but there's trouble brewing in Bedrock-- an evil executive and his sinister secretary are now plotting to use Fred as the fall guy in an embezzlement scheme.